2008
DOI: 10.1177/0269881108095705
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enhances processing of positive versus negative emotional information in healthy male volunteers

Abstract: Animal studies have shown the role of oxytocin in affiliation and attachment, and recent evidence suggests that oxytocin is also involved in human models of approach behaviour, possibly by modulating the processing of emotionally valenced stimuli. Although oxytocin administration has been reported to decrease neural responses to facial emotional information, the effects on a wider range of behavioural measures of emotional processing shown to be sensitive to antidepressant manipulation have not been examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
155
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(181 citation statements)
references
References 47 publications
19
155
1
2
Order By: Relevance
“…OT renders social decisions less responsive to the immediate social environment and more consistent with preexisting preferences (5,26). OT magnifies preexisting biases in emotion classification (27) and in-group/outgroup decision biases in economic games (7). In the macaque, OT also increases both prosocial and selfish choices in a reward allocation task, magnifying the preferences observed in the absence of OT (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OT renders social decisions less responsive to the immediate social environment and more consistent with preexisting preferences (5,26). OT magnifies preexisting biases in emotion classification (27) and in-group/outgroup decision biases in economic games (7). In the macaque, OT also increases both prosocial and selfish choices in a reward allocation task, magnifying the preferences observed in the absence of OT (4).…”
Section: Discussionmentioning
confidence: 99%
“…In the macaque, OT also increases both prosocial and selfish choices in a reward allocation task, magnifying the preferences observed in the absence of OT (4). Moreover, OT slows response times for accurately identifying facial expressions (13,27) and for making social decisions in the presence of others (4). These results indicate that less information about the immediate social context may be available for decision processes following OT.…”
Section: Discussionmentioning
confidence: 99%
“…Single doses of intranasal oxytocin can also produce prosocial, anxiolytic, and affiliative effects in healthy adults (Bos et al, 2011;Lim and Young, 2006). For example, oxytocin has been shown to increase trust and generosity (Kosfeld et al, 2005;Zak et al, 2007), reduce responses to social stressors (Heinrichs et al, 2003), increase positive communication (Ditzen et al, 2009), and, like MDMA, enhance recognition of positive emotional states and dampen responses to negative emotions in others (Di Simplicio et al, 2009;Domes et al, 2007a,b;Marsh et al, 2010;Shahrestani et al, 2013). On the other hand, other studies have failed to detect prosocial effects of oxytocin, and indeed, found that it can produce antisocial effects such as feelings of envy and mistrust (Bartz et al, 2011a;Declerck et al, 2010;Shamay-Tsoory et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pre Oxford Emotional Test Battery (ETB) for detecting potential antidepressant efficacy have been validated over a period of more than 10 years in studies with both positive controls [25][26][27][28][29][30][31][32][33][34][35] , and negative controls 36,37,38 in healthy volunteers and in patients with depression …”
Section: Initial Findings and Lessons Learnedmentioning
confidence: 99%